Voluntary ‘organic’ leadership for community resilience - Lough, Benjamin J. (Voluntary sector review, 2021)
This article investigates the qualities of bottom-up leadership that emerges voluntarily and collectively in response to adverse events. With an eye on better understanding the resilience of marginalised communities in the Global South, it seeks to illustrate how bottom-up ‘organic’ leadership is a clear manifestation of place leadership at the local level. Findings are drawn from qualitative field data gathered in 10 Southern communities. These data illustrate that people are often willing and able to organise organically in response to adversity – and are largely successful at navigating the complex challenges they encounter. However, the long-term sustainability of organic leadership in self-organised groups often requires balanced supports from external actors. Better recognition of the added value of voluntary self-organisation happening in vulnerable communities can provide a platform for more innovative, experimental and co-creative solutions to manage risk.